Effect of castration on carcass and meat quality attributes in native lambs of Bangladesh - Hossain, MA; Numan, AA; Haque, ME; Haque, MR; Rahman, MM; Hashem, MA (Meat Research, 2022)
The aim of this study was to examine the effect of castration on carcass traits and meat quality of three native region lambs. The selected sixty lambs were divided into two groups like T1 (Uncastrated) and T2 (Castrated) having 30 lambs of each group. Statistical analysis was conducted by SAS with 3×2 factorial experimental model in Completely Randomized Design (CRD). Parameter studied were carcass traits, proximate component (DM, CP, EE, and Ash), physicochemical (ultimate pH, cooked pH, cooking loss, drip loss, water holding capacity- WHC), sensory attributes (color, flavor, tenderness, juiciness, overall acceptability) and instrumental color values (CIE L*, a* and b*). The lamb type and castration had significant effect (p<0.001) on ADG, hot carcass, CP, EE, flavor, juiciness and b* values of native region lambs. The lamb type had significant effect (p<0.001) on drip loss, cooked pH, tenderness and a* values of native region lambs. The ADG and hot carcass were significantly higher (p<0.001) in uncastrated groups than castrated groups. The CP and EE% were significantly higher (p<0.001) in castrated groups than uncastrated groups. Significant higher flavor was found in castrated group whereas juiciness was higher in uncastrated group. It may be concluded that uncastrated lambs showed better in productive performance and carcass traits but castrated lambs showed better in meat quality attributes as evidence from proximate components, physicochemical traits and sensory attributes. Hence, JBL showed better performances among three native region lambs of Bangladesh.